Revision of the NMR assignments of pterostlbene and of dihydrodehydrodiconiferyl alcohol: Cytotoxic constituents from anogeissus acuminata - Agnes M. Rimando (2018)
Further phytochemical work on Anogeissus acuminata var. lanceolata (Combretaceae) led to the isolation of pterostiibene (1), dihydrodehydrodiconifery! alcohol (2), and conocarpan (3). The structure of these compounds were determined by spectroscopic means, mainly through ID and 2D NMR experiments. A revision of some of the 13 C NMR chemical shifts of 1 and 2 were made possible by HETCOR, FLOCK, and selective INEPT experiments. Homonuclear spin-decoupling and 'H^H COSY experiments also enabled the precise assignment of the 'H NMR chemical shifts of 2. Compounds 1–3 exhibited in vitro cytotoxicity in various cancer cell lines. This is the first isolation of 1–3 from Anogeissus. © 1994, Taylor & Francis Group, LLC. All rights reserved.